Influence of residual stress distribution and microstructural characteristics on fatigue failure mechanism in Ni‐based Superalloy. Issue 6 (28th March 2021) - Kumar, Dharmesh; Idapalapati, Sridhar; Wang, Wei
Abstract: The influence of residual compressive stress (RCS) depth and magnitude generated through surface treatments such as shot peening (SP), deep cold rolling (DCR), and vibro‐peening (VP) on fatigue crack mechanisms of Ni‐based superalloy is investigated. The fatigue performance with associated failure mechanisms is measured under strain‐controlled fatigue testing upto 10 4 cycles with total strain in the range of 0.9%–1.4% at an R ratio of 0.1 and 400°C followed by load controlled fatigue until failure. In‐depth understanding of the failure mechanism is obtained through fractography analysis, cyclic stress–strain plot, and microstructural features. A pronounced improvement in fatigue life tested at low strain range (0.9%–1.1%) is achieved after inducing RCS up to 400 μm depth. However, the fatigue life is reduced when RCS increased to 800–1000 μm depth. Failure is primarily driven by micro‐cracks formed due to balancing tensile stresses and high intensity stress concentration generated as the result of dislocation pile‐ups and slip bands. Results are discussed in detail through the evidence of grain refinement, addition of low angle grain boundaries (LAGBs), strain accumulation, and intragranular deformation in the sub‐surface.